Direct measurement of surface-induced orientational order parameter profile above the nematic-isotropic phase transition temperature. - Lee, Ji-Hoon.; Atherton, Timothy J.; Barna, Valentin.; De Luca, Antonio.; Bruno, Emanuela.; Petschek, Rolfe G.; Rosenblatt, Charles. (Tufts University. Tisch Library., 2017)
The spatial and temperature dependence of the surface-induced orientational order parameter S(z,T) was determined in the isotropic phase. An optical fiber was immersed in a thin liquid crystal layer and the retardation was measured as a function of the fiber's height above the surface, from which the model-independent S(z,T) was deduced with resolution ≲2  nm. It was found that (i) S(z=0)≲0.12 close to the nematic transition temperature, (ii) the susceptibility is mean-field-like, and (iii) S(z,T) deviates significantly from exponential spatial decay. The results are discussed in terms of a nonlocal potential.